2013
DOI: 10.1093/ije/dyt109
|View full text |Cite
|
Sign up to set email alerts
|

Risk of childhood undernutrition related to small-for-gestational age and preterm birth in low- and middle-income countries

Abstract: Background Low- and middle-income countries continue to experience a large burden of stunting; 148 million children were estimated to be stunted, around 30–40% of all children in 2011. In many of these countries, foetal growth restriction (FGR) is common, as is subsequent growth faltering in the first 2 years. Although there is agreement that stunting involves both prenatal and postnatal growth failure, the extent to which FGR contributes to stunting and other indicators of nutritional status is uncertain. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
387
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 459 publications
(442 citation statements)
references
References 47 publications
28
387
0
9
Order By: Relevance
“…The prevalence of underweight was significantly higher at Age 5 in both sexes, and the multiple regression analysis indicated that SGA at birth was only associated with underweight in 5-year-old children. Indeed, a review of childhood undernutrition risk based on SGA and preterm birth found that SGA, irrespective of gestational age, was risk factor for underweight at 12 -60 months compared with AGA or term births [34].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of underweight was significantly higher at Age 5 in both sexes, and the multiple regression analysis indicated that SGA at birth was only associated with underweight in 5-year-old children. Indeed, a review of childhood undernutrition risk based on SGA and preterm birth found that SGA, irrespective of gestational age, was risk factor for underweight at 12 -60 months compared with AGA or term births [34].…”
Section: Discussionmentioning
confidence: 99%
“…SGA is an indicator of intrauterine growth restriction and, together with prematurity, constitutes a risk factor for fetal, neonatal, and infant mortality, and negative consequences on health in the long term. 3,4 There is no international consensus on anthropometric analysis among preterm newborns. The National C o m m i t t e e o n G r o w t h a n d Development (Comité Nacional de Crecimiento y Desarrollo) and the Fetoneonatal Study Committee (Comité de Estudios Fetoneonatales) have proposed the curves obtained by Fenton and Kim for preterm newborn infants (NBIs) follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term undernutrition among pregnant mothers is associated with uterus volume and it is a predictor for fetus growth and birth size (low birth weight and length) (Christian et al, 2013).…”
Section: Effects Of Maternal Nutritionalmentioning
confidence: 99%